Not for the Profit, but for the Training? Gender Differences in Training in the For-Profit and Non-Profit Sectors - Benoît Dostie; Mohsen Javdani (Institute of Labor Economics (IZA), 2017)
We use Canadian linked employer-employee data to examine gender differences in probability, duration, and intensity of firm-sponsored training. We find that women in the for-profit sector are less likely to receive classroom training, and receive shorter classroom training courses. However, we find the reverse in the non-profit sector, with women being more likely to receive both classroom and on-the-job training, and also receiving longer classroom training courses. Our results suggest that women's worse training opportunities in the for-profit sector mainly operate within workplaces. We find no evidence that gender gaps in training in the for-profit sector are driven by lower probabilities of accepting training offers, child or family commitments, weaker labour market attachment, or worker self-selection. We also find that gender differences in expected changes in wages and training opportunities between the two sectors can explain a large portion of women's higher probability of employment in the non-profit sector. Finally, decomposition results suggest that gender differences in training explain some of the gender wage gap in the for-profit sector, which is twice as large than in the non-profit sector.
Keywords: J24; L22; M53; O32; 330; gender; non-profit; firm-sponsored training; linked employer-employee data; gender wage gap